Phenotypic detection of methicillin-resistant Staphylococcus aureus in village chickens from poultry markets in Maiduguri, Nigeria - Kwoji, Iliya Dauda; Jauro, Solomon; Musa, Jasini Athanda; Lekko, Yusuf Madaki; Salihu, Sabo Isa; Danchuwa, Hassan Abdullahi (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The study was carried out to detect the carriage of methicillin-resistant Staphylococcus aureus (MRSA) and their antimicrobial susceptibilities in village chickens sold at Maiduguri poultry markets using phenotypic characterization. Materials and Methods: This was a cross-sectional study where 120 samples comprised 50% each of Nasal and cloacal swabs, were, respectively, collected from live village chickens sold at Maiduguri poultry markets and examined for the presence MRSA based on bacterial culture, biochemical characteristics, growth on oxacillin resistant screening agar base, and antimicrobial susceptibility tests. Results: The study revealed an overall occurrence of 38.33% S. aureus and 32.60% MRSA, respectively. Antimicrobial susceptibility test was carried out on MRSA positive isolates against seven antimicrobials. All the isolates (100%) exhibited resistance against cefoxitin, whereas the least antimicrobial resistance was recorded against erythromycin and streptomycin each with 26.6%, respectively. In the same way, the highest antibiotic susceptibility in this study was observed against erythromycin (60%) and least susceptibility was against vancomycin and streptomycin with 20% each. A varying intermediate antibiotic susceptibility ranging from 13.33% to 53.33% was observed. Multiple-drug resistance patterns were exhibited by MRSA isolates from this study with 73.3% of the isolates exhibiting resistance to two or more antibiotics. Conclusion: This study has shown the carriage of MRSA by village chickens which calls for serious public health concern and concludes that these birds might have acquired these pathogens from the environment or infected humans since they normally receive no less medical attention. J. Adv. Vet. Anim. Res., 6(2): 163-167, June 2019